Relationship Between Academic Self-Concept and Academic Achievement of Distance Learners: Muhammad Ajmal, Mariam Rafique (PJDOL, 2023)
The purpose of the study was to find the relationship between academic self-concept and academic achievement of distance learners. The academic self-concept of distance learners was measured by the Liu and Wang (2005) academic self-concept scale which was adapted by the present researcher. T